Determinant of Islamic banking instituitions' profitability in Malaysia / Nurul Najwa Yahya - Yahya, Nurul Najwa (Faculty of Business Management, 2016)
The aim of this study is to examine the Islamic bank‟s profitability in Malaysia over the time period from 2012 to 2015 which is 4 years period of study. This paper was selected 10 Islamic banks in Malaysia. The bank profitability is measured by Return on Equity (ROA) which is to look at the profitability of the bank. There have five selected independent variables in this study that consist of bank size, operational efficiency, liquidity, credit risk and capital adequacy.This study used multiple regression model represented by the ordinary least squares (OLS) since the result shows it better then panel data regression model as the technique to look factor that affect the Islamic Bank‟s profitability in Malaysia. The result shows that only bank size and operational efficiency have a positive relationship and significant effect on bank probability. Therefore, another independent variable shows negative relationship and not significant. These results suggest that banks can improve their profitability through increasing bank asset and decreasing loan to debt and credit risk.